1998
DOI: 10.1136/jnnp.64.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relapses and disease activity on magnetic resonance imaging associated with viral upper respiratory tract infections in multiple sclerosis

Abstract: Background-Although the risk of clinical attacks of multiple sclerosis seems to be significantly increased with viral upper respiratory tract infections (URTI), serological evidence for the reported association remains controversial. In addition, although MRI is six to 10 times more sensitive than clinical exacerbations in indexing disease activity, any possible association between URTI and MRI activity has yet to be investigated. Objectives-To examine the relation between URTI and disease activity, in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
108
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 42 publications
7
108
2
1
Order By: Relevance
“…Breakdown of the BBB has been reported in a clinical study by Edwards et al (1998) in MS patients during periods of infection. In contrast, in the more recent study by Buljevac et al (2002), peripheral infection did not appear to alter the number of contrast-enhancing lesions in MS patients, although changes in the spatial extent of existing lesions were not considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breakdown of the BBB has been reported in a clinical study by Edwards et al (1998) in MS patients during periods of infection. In contrast, in the more recent study by Buljevac et al (2002), peripheral infection did not appear to alter the number of contrast-enhancing lesions in MS patients, although changes in the spatial extent of existing lesions were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence that there may be a link between infection and relapse (Buljevac et al, 2002). A number of studies have shown that approximately one-third of MS relapses are preceded by a viral infection (Sibley et al, 1985;Andersen et al, 1993;Panitch, 1994;Edwards et al, 1998;Buljevac et al, 2002). Relapse in individuals with MS has also been associated with bacterial infections, such as those of the urinary tract, which appear to trigger relapse in as many as 30% of MS patients (Rapp et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial infection is the environmental factor most strongly associated with exacerbations of MS as well as other autoimmune diseases (26,(61)(62)(63). Furthermore, mice that are transgenic for a myelin-specific TCR develop spontaneous EAE when housed in a nonsterile facility, but not in a sterile, specific pathogen-free facility (64).…”
Section: Discussionmentioning
confidence: 99%
“…n certain autoimmune diseases, including diabetes, myocarditis, and herpes stromal keratitis, microbial infections often precede the onset of clinical disease (1)(2)(3)(4), or correlate with relapses, most notably in the case of multiple sclerosis (MS) 3 (5)(6)(7)(8). MS, a common chronic inflammatory disease of the CNS, is characterized by periodic relapses of neurological disease (9).…”
mentioning
confidence: 99%